Factors affecting pulsatile ocular blood flow in normal subjects - Mori, F (2001)
BACKGROUND—The factors that influence pulsatile ocular blood flow (POBF) were evaluated in normal subjects. METHODS—POBF was measured in 80 normal subjects using Langham OBF computerised tonometry. The effect of age, systolic and diastolic blood pressure, refractive error, intraocular pressure, and axial length on POBF was evaluated using multiple regression analysis. RESULTS—The mean (SD) POBF value was 593.3 (203.6) µl/min (range 290.7-1201.6). Of all the independent variables in the model, only the axial length was statistically significant (p=0.008). The regression coefficient was negative, indicating that the axial length decreased with increasing POBF. CONCLUSIONS—These data suggest that, in normal subjects, the POBF decreases as axial length increases. Choroidal blood flow may decrease as the axial length increases. The axial length may therefore be a major factor affecting POBF.